Optimasi Sintesa Nanokoloid Human Serum Albumin sebagai Agen Limfoskintigrafi Menggunakan Central Composite Design-Response Surface Methodology - Lestari, Wening; Setiyowati, Sri; Triningsih, Triningsih; Asyikin, Khoirunnisa Fauziah; Suharmadi, Suharmadi; Mujamilah, Mujamilah; Sulungbudi, Grace Tjungirai; Juliyanto, Sumandi (Jurnal Kefarmasian Indonesia, 2022)
The prevalence of cancer in Indonesia is increasing and various cancer treatments still have shortcomings, cancer recurrence still occurs. Lymphoscintigraphy is a method for detecting disorders of the lymphatic system, which are closely related to cancer cells. Human serum albumin nanocolloid as a lymphoscintigraphic agent consists of particles measuring